An Experimental Approach to Rigorously Assess Paneth Cell α-Defensin (Defa) mRNA Expression in C57BL/6 Mice - Patricia A. Castillo (Nature Portfolio, 2019)
Abstract Abundant evidence from many laboratories supports the premise that α-defensin peptides secreted from Paneth cells are key mediators of host-microbe interactions in the small intestine that contribute to host defense and homeostasis. α-defensins are among the most highly expressed antimicrobial peptides at this mucosal surface in many mammals, including humans and mice; however, there is striking variation among species in the number and primary structure of α-defensin paralogs. Studies of these biomolecules in vivo are further complicated by striking variations between laboratory mouse strains. Herein, we report an experimental approach to determine with precision and specificity expression levels of α-defensin (Defa) mRNA in the small intestine of C57BL/6 mice through an optimized set of oligonucleotide primers for qRT-PCR assays and cloned cDNA plasmids corresponding to the Defa paralogs. This approach demonstrated marked differences in α-defensin expression in C57BL/6 mice with respect to proximal/distal anatomical location and developmental stage, which have not been described previously. These data underscore the importance of careful attention to method (primer choice, proximal vs. distal location, and developmental stage) in analysis of antimicrobial peptide expression and their impact.